DEVELOPMENT OF STROKE PREVENTIVE CARE MODEL FOR OLDER PERSONS IN A PRIMARY CARE CONTEXT (Proceedings of the International Conference on Public Health, 2017)
Stroke is a major cause of long-term disability among Thai older persons. Stroke prevention at a primary care level is an effective solution to this problem. This action research aimed to develop stroke preventive care model for older persons in the primary care context. Forty three participants were stakeholders of a community health system in the northeastern part of Thailand. Data were collected through in-depth interviews, and focus group discussions. They were analyzed using content analysis, and were validated through data triangulation. The research process comprised of 3 phases: situation analysis; development process and model synthesis.  Results showed “The Integrated Stroke Preventive Care Service Model (ISPCSM)” comprised of 7 keys preventive activities which were: 1) community awareness raising and proactive screening; 2) risk behaviors modification; 3) proactive NCDs clinic; 4) stroke warning management; 5) strengthening stroke fast track; 6) stroke rehabilitation; and 7) integrated home care. The ISPCSM for community elders required the integration of care services among stakeholders of the primary care context at all stages of stroke prevention (primary, secondary, tertiary).
Keywords: action research, model development, older person, stroke prevention